Pengembangan Media Pembelajaran Interaktif untuk Sekolah Menengah Atas Kelas XI pada Pokok Bahasan Momentum - Sri Rezeki; Ishafit Ishafit (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2017)
Abstract This research is aimed to developing interactive learning media physics for high school class XI with chapter of momentum and test the feasibility of interactive learning media through media expert validation and subject experts. Based on the evaluation of the validator (media specialists and subject experts), the media of the development of aspects of the product appearance and usefulness aspects of the product got a score average of 80.23% is included in the category of Most Eligible. Based on the results of the validation assessment of media experts, media development results are included in the category of Most Eligible with the feasibility level of 81.98%. Based on the validation results subject experts, media development results included in the category of Eligible with the feasibility level of 78.47%. Based on the results of the response of students scored an average 74.63% included in the category of Eligible. Based on the assessment, it can be concluded that, media interactive learning on the subject of momentum declared fit for use as a medium of learning physics class XI high school student. Keywords: media interactive learning, physics education, learning strategies, high school. Abstrak Penelitian pengembangan ini bertujuan untuk mengembangkan media pembelajaran fisika interaktif untuk sekolah menengah atas kelas XI materi momentum dan menguji kelayakan media pembelajaran interaktif melalui validasi ahli media dan ahli materi. Berdasarkan hasil penilaian dari para validator (ahli media dan ahli materi), media hasil pengembangan dari aspek penampilan produk dan aspek kemanfaatan produk mendapat skor rerata 80.23% yang termasuk dalam kategori Sangat Layak. Berdasarkan hasil penilaian validasi ahli media, media hasil pengembangan termasuk dalam kategori Sangat Layak dengan tingkat kelayakan 81.98%. Berdasarkan hasil validasi ahli materi, media hasil pengembangan termasuk dalam kategori Layak dengan tingkat kelayakan 78.47%. Berdasarkan hasil respon peserta didik mendapat skor rerata 74.63% termasuk dalam kategori Layak. Berdasarkan penilaian yang telah dilakukan dapat disimpulkan bahwa, media pembelajaran interaktif pada pokok bahasan momentum dinyatakan layak digunakan sebagai media pembelajaran fisika untuk siswa kelas XI Sekolah Menengah Atas. Kata-kata kunci: media pembelajaran interaktif, pendidikan fisika, strategi pembelajaran, sekolah menengah.